Pengaruh Senam Zumba Terhadap Profil Antropometri dan Mean Arterial Pressure pada Mahasiswa Obesitas Universitas Lampung - Lesilolo, Caroline Virgine Putri; Berawi, Khairun Nisa (CV. Jasa Sukses Abadi, 2024)
Obesity contributes for about 2.8 deaths each year and has an effect on increasing blood pressure. The prevalence of obesity in Indonesia in 2018 in adults was 21.8% and is predicted to continue to increase every year. Zumba exercise is an aerobic exercise that is proven to be effective in reducing body fat percentage by burning calories from body fat stores and effective in lowering blood pressure. Seeing the great benefits of Zumba gymnastics but the still limited research on the influence of Zumba gymnastics on the anthropometric profile and Mean Arterial Pressure (MAP) in obese individuals, researchers are interested in conducting research on the influence of Zumba gymnastics intervention on the anthropometric profile and MAP in students at the University of Lampung who are obese. This research is a quasi experimental design with a non-randomized control group pretest-posttest approach. The samples used is 26 samples for each zumba group with zumba fitness exercise treatment and the control group without zumba exercise treatment, which were taken by purposive sampling technique. The analysis is using a paired t-test parametric test and non-parametric wilcoxon test. The results showed that zumba exercise had a significant effect on the anthropometric profile Body Mass Index (BMI) with p-value = 0.000, abdominal circumference with p-value = 0.000, and MAP with p-value = 0.000. Based on the statistical results, there is a significant effect of zumba exercise on BMI, abdominal circumference, and MAP in obese students of Lampung University.